Adoption Of the Precautionary Principle on the Safety and Health Risks of Nanofood in Malaysia - Hasmin, Nor Akhmal; Zainol, Zinatul Ashiqin; Mahmood, Anida; Matmin, Juan (UUM Press, 2024)
Food derived from nanotechnology or contains engineered nanomaterials (ENMs) is widely available for consumers in the marketplace. Oral exposure to ENMs has been linked to various potential adverse effects on human safety and health. In Malaysia, nanofood is regulated with a regulatory framework designed for conventional food without considering the unique and novel properties of ENMs. The adequacy of the existing framework for regulating the safety and health risks of nanofood is ambiguous. This study examined the necessity for Malaysia of having such regulatory framework to govern the safety and health risks of nanofood using the precautionary principle. By adopting the doctrinal analysis, the finding suggests that the existing food safety framework must be amended to incorporate specific provisions on nanotechnology, and that the amendment must be based on the precautionary principle. The new regulatory framework enables the food safety authority to implement the earliest precautionary measure, protecting consumers from serious future harm caused by nanofood. The proposed regulatory framework will strengthen the domestic food safety framework and national food safety policy in meeting the challenge posed by nanofood.